2003
DOI: 10.1159/000069959
|View full text |Cite
|
Sign up to set email alerts
|

Histometric Assessment of Psoriatic Plaques Treated by Vitamin D<sub>3</sub> Derivatives

Abstract: Background: Psoriasis is an immunogenetic disorder. Factor XIIIa+ dermal dendrocytes (DD) are part of the pathobiological changes in the plaque type of the disease. Objective: The present study aimed at comparing the effect of 3 vitamin D3 derivatives on the epidermis, microvasculature and DD in psoriasis. Method: Twenty men suffering from chronic plaques of psoriasis on the trunk were enrolled in this study. They applied twice a day for 3 weeks calcipotriol, tacalcitol and calcitriol, each to one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…80 Vitamin D analogs are effective treatments and are widely used as drugs for hyperproliferative skin disorders such as psoriasis, and in suppression of secondary hyperparathyroidism and parathyroid hyperplasia resulting from chronic renal insufficiency. [107][108][109] For instance, Gemini analogs have been recently found to be 100 -1000 times more potent in their antiproliferative activity than the natural hormone. Studies in mice suggest that they may be useful in the treatment of some cancers, including colon cancer.…”
Section: Vitamin D Analogs For Cancer Treatmentmentioning
confidence: 99%
“…80 Vitamin D analogs are effective treatments and are widely used as drugs for hyperproliferative skin disorders such as psoriasis, and in suppression of secondary hyperparathyroidism and parathyroid hyperplasia resulting from chronic renal insufficiency. [107][108][109] For instance, Gemini analogs have been recently found to be 100 -1000 times more potent in their antiproliferative activity than the natural hormone. Studies in mice suggest that they may be useful in the treatment of some cancers, including colon cancer.…”
Section: Vitamin D Analogs For Cancer Treatmentmentioning
confidence: 99%
“…One study focusing on the effects of both topical vitamin D derivatives on cultured keratinocytes showed that both calcitriol and calcipotriol inhibited the keratinocyte proliferation, induced the cornified envelope formation and had no effect on keratin (K) 5 and K1 expression 9 . Another study reported a significant reduction in factor XIII expressing dermal dendritic cells after treatment with calcitriol, but not after treatment with calcipotriol 13 . Finally, a flow cytometric study on keratinocytes by Franssen et al 7 .…”
mentioning
confidence: 99%
“…Calcipotriol is a vitamin D 3 derivative active on the keratinocyte biology 8 . Its therapeutic effects have been demonstrated particularly in psoriasis 8–10 . Some in vitro effects on the human melanocyte biology have also been documented, 11–16 but its in vivo effects on the epidermal melanocyte unit 7,17 are largely unknown.…”
Section: Introductionmentioning
confidence: 99%